Effectiveness of Manualised Interpersonal Problem-Solving Skills Intervention for Children with Autism Spectrum Disorder (ASD) - Bonete, Saray; Molinero, Clara; Mata, Sara; Calero, Mª; Gómez-Pérez, Mª. (Psicothema, 2016)
Background: Children with Autism spectrum disorders (ASD) frequently present a deficit in interpersonal and social problem solving skills. The Interpersonal Problem-Solving Skills Programme for Children (SCI-Children) comprises 10 weekly, one hour sessions working on interpersonal abilities from a mediation strategy for training purposes. Method: The first study explores the effectiveness of training through pre- and post-treatment evaluations of a sample of 22 children with ASD (7-13 years of age). The second study replicates the programme with 15 children who were assessed three times (three months before the programme starts, at the beginning of the training and at the end of it). Results: In the first study, significant differences were found in outcome measures (a parent-report subscale of a socialisation measure and child performance on one subscale and total scores of an interpersonal problem-solving skills task). Results in the second study showed no significant changes in absence of the treatment during the waiting period and significant changes after the treatment in the socialisation measure. Conclusions: These findings suggest that the SCI-Children program causes positive impact on the participants. Further evaluation is warranted.